A retrospect and outlook on the neuroprotective effects of anesthetics in the era of endovascular therapy - Zhang, Tianhao; Deng, Daling; Huang, Shiqian; Fu, Daan; Wang, Tingting; Xu, Feng; Ma, Lulin; Ding, Yuanyuan; Wang, Kaixin; Wang, Yafeng; Zhao, Wenjing; Chen, Xiangdong (Frontiers in Neuroscience, 2023)
Studies on the neuroprotective effects of anesthetics were carried out more than half a century ago. Subsequently, many cell and animal experiments attempted to verify the findings. However, in clinical trials, the neuroprotective effects of anesthetics were not observed. These contradictory results suggest a mismatch between basic research and clinical trials. The Stroke Therapy Academic Industry Roundtable X (STAIR) proposed that the emergence of endovascular thrombectomy (EVT) would provide a proper platform to verify the neuroprotective effects of anesthetics because the haemodynamics of patients undergoing EVT is very close to the ischaemia–reperfusion model in basic research. With the widespread use of EVT, it is necessary for us to re-examine the neuroprotective effects of anesthetics to guide the use of anesthetics during EVT because the choice of anesthesia is still based on team experience without definite guidelines. In this paper, we describe the research status of anesthesia in EVT and summarize the neuroprotective mechanisms of some anesthetics. Then, we focus on the contradictory results between clinical trials and basic research and discuss the causes. Finally, we provide an outlook on the neuroprotective effects of anesthetics in the era of endovascular therapy.